The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.7196/samj.2018.v108i10.13207
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal listeriosis during a countrywide epidemic in South Africa: A tertiary hospital’s experience

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Mortality rate in this study was 26%, similar to that observed in another tertiary hospital in South Africa during the similar outbreak. 9 Listeriosis is known to have an average case-fatality rate of 20%-30% despite adequate antimicrobial treatment. The frequency of abortion and stillbirth increases the overall mortality rate to >50%, 24 although this was not looked at in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality rate in this study was 26%, similar to that observed in another tertiary hospital in South Africa during the similar outbreak. 9 Listeriosis is known to have an average case-fatality rate of 20%-30% despite adequate antimicrobial treatment. The frequency of abortion and stillbirth increases the overall mortality rate to >50%, 24 although this was not looked at in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The infants are often born preterm, and the mean postnatal age at onset of symptoms for early-onset disease is 1.5 days. 8,9 Clinical presentations of neonatal listeriosis include septicemia (81%-88%), respiratory distress or pneumonia (38%), meningitis (24%) and more rarely myocarditis and granulomatosis infantisepticum. [10][11][12] Neonatal disease and outcomes are often more severe in contrast to mild maternal disease.…”
mentioning
confidence: 99%
“…Interestingly, the first reported case of listeriosis was an isolation of LMO from the cerebrospinal fluid (CSF) of a four-year-old immunocompromised child in Africa by Benallegue et al (1968) . Subsequently, cases of neonatal listeriosis have been reported in Algeria ( Ramdani-Bouguessa and Rahal, 2000 ), Tunisia ( Fendri et al, 1989 ) and South Africa ( Dramowski et al, 2018 ). Researchers have conducted several studies in African countries following numerous reported infections with strong clinical symptoms.…”
Section: Characteristics and Distribution Of Listeriamentioning
confidence: 99%
“…Despite considering L. monocytogenes as a part of the faecal microbiota in most mammals, up to 5% of healthy animals should be taken into consideration as the asymptomatic carriers [16]. It seems that the study on human (as the permanent reservoir of L. monocytogenes) microbiota samples including intestines, vagina, milk, and urine have not taken into consideration as well as human-to-human transmission routs [16][17][18]. Given the importance of L. monocytogenes infection connected to pregnant women and its consequences in pregnancy, this study, based on the type of samples, used the vaginal swabs to detect L. monocytogenes infections.…”
Section: Introductionmentioning
confidence: 99%